Open Science – For Whom?. (10th January 2022) - Dominik, Martin; Nzweundji, Justine Germo; Ahmed, Nova; Carnicelli, Sandro; Mat Jalaluddin, Nurzatil Sharleeza; Fernandez Rivas, David; Narita, Vanny; Enany, Shymaa; Rios Rojas, Clarissa
Who can participate in Open Science and whose interests are served? Open Science in principle holds the potential to reduce inequality, but this is not going to happen unless it operates within a consistent framework and environment that supports this goal. Unequal power and opportunities from institutional to global level constitutes a major obstacle to human development, while we need to appreciate diversity as a key asset. How can we build an equitable global research ecosystem in accordance with the United Nations 2030 Agenda for Sustainable Development that recognises science as a global common good and an integral part of the shared cultural heritage of humankind?